Bioprinting of 3D hydrogels. Issue 15 (7th August 2015) - Stanton, M. M.; Samitier, J.; Sánchez, S.
<x xml:space="preserve">Abstract</x> This article focuses on bioprinting utilizing hydrogels as 3D scaffolds.